Nursing Care Process in a Woman with Low Therapeutic Adherence to Chronic Disease Treatment (Boletín Semillero de Investigación en Familia, 2025)
Introduction: Nursing, as a science with its own object and methods, carries out its professional practice through theories and models that guide systematic and contextualized interventions. These interventions strengthen disciplinary knowledge and contribute to the improvement of quality of lifeand health of care recipients. Objective: To provide health care to an older adult woman with chronic multimorbidity and low level of therapeutic adherence. Materials and Methods: The five phases of the nursing care process were implemented: assessment, diagnosis, planning, implementation, and evaluation. Results: A comprehensive approach was carried out based on nursing theories, including Gordon’s Functional Health Patterns, Orem’s Self-Care Model, and Roy’s Adaptation Model. Ineffective behaviors in health maintenance were identified, associated with lack of knowledge, poor therapeuticadherence, and limited coping capacity. The care plan focused on health education, strengthening selfcare,encouraging active participation of the family network, and improving access to health services. Conclusion: The application of the nursing care process facilitated an understanding of the patient’s health status and adaptation barriers, improving habits, support networks, and access to services through the integration of nursing theoretical models and health education.
Keywords: Nursing; Nursing process; Chronic disease; Patient care planning; Health education